2021
DOI: 10.1097/meg.0000000000002129
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of P-wave dispersion and left atrial functions assessed with three-dimensional echocardiography in patients with cirrhosis

Abstract: Background Cirrhotic cardiomyopathy (CCM) is a well-known entity. The aim of this study was to compare left atrial three-dimensional (3D) volume and P-wave dispersion (PWd) in patients with cirrhosis and a healthy population. The secondary purpose was to assess the left phasic volumes and reservoir functions with 3D echocardiography for the prediction of an increased risk of poor outcomes in patients with cirrhosis. Methods The study included 50 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In recognition of the importance of physical activity in preventing sarcopenia, obesity and general well-being in CD 37 , 38 we employed wearable sensors to determine the physical activity levels of our study participants. Notably, while our initial expectation was that physical activity may be lower in the CD setting overall and especially in relapse 39 , our results showed a general level of activity in line with, or exceeding, that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In recognition of the importance of physical activity in preventing sarcopenia, obesity and general well-being in CD 37 , 38 we employed wearable sensors to determine the physical activity levels of our study participants. Notably, while our initial expectation was that physical activity may be lower in the CD setting overall and especially in relapse 39 , our results showed a general level of activity in line with, or exceeding, that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…35 LA volume is a sign of diastolic and systolic dysfunction and a marker of atrial remodeling. 36 Prolonged PWPT, PWD, PWdis, and abnormal PWTF have all been linked to PAF in previous studies. 15,16 Sato et al found reduced PWD and PWdis after dapagliflozin treatment and attributed the effect to volume changes in epicardial adipose tissue.…”
Section: Discussionmentioning
confidence: 81%
“…LA enlargement and decreased LA function are predictors of atrial fibrillation, stroke, and death 35 . LA volume is a sign of diastolic and systolic dysfunction and a marker of atrial remodeling 36 . Prolonged PWPT, PWD, PWdis, and abnormal PWTF have all been linked to PAF in previous studies 15,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Other studies have reported no difference in baseline cardiac echo findings, in terms of mortality or AKI in the long-term follow-up of cirrhosis. 15,16 Since the LV dimensions in the two groups (e.g., median LV dimensions of 40 mm in the mortality and 43 mm in the non-mortality groups) were similar, with a slight statistical difference between them. Based on this cohort's LV dimensions, it would seem that the clinical utility of this measurement would be limited.…”
Section: Discussionmentioning
confidence: 97%